1998
DOI: 10.2355/isijinternational.38.390
|View full text |Cite
|
Sign up to set email alerts
|

Positive Growth of Phytoplankton under Conditions Enriched with Steel-making Slag Solution.

Abstract: The growth ability of 12 species of phytoplankton was examined in culture media enriched with steel-making slag soiution at various concentrations, Since a highly significant linear regression of the in vivo fluorescence (lVF) of cell suspension against absolute chlorophyll a concentration was established, the growth ability was determined quickly by IVF. Under the enriched conditions all the species examined showed positive growth, although in different manners. Based on the specific differences in the optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Takayuki FUTATSUKA, Kiyoteru SHITOGIDEN, 1) Takahiro MIKI, 2) Tetsuya NAGASAKA 3) and Mitsutaka HINO 2) Formerly Graduate Student, Graduate School of Engineering, Tohoku University, now at JFE Steel Corp. 1) Formerly Graduate Student, Graduate School of Engineering, Tohoku University, now at Nippon Yakin Kogyo Corp. 2) Department of Metallurgy, Graduate School of Engineering, Tohoku University, Aoba-yama 02, Sendai 980-8579 Japan.…”
Section: Dissolution Behavior Of Nutrition Elements From Steelmaking mentioning
confidence: 99%
See 1 more Smart Citation
“…Takayuki FUTATSUKA, Kiyoteru SHITOGIDEN, 1) Takahiro MIKI, 2) Tetsuya NAGASAKA 3) and Mitsutaka HINO 2) Formerly Graduate Student, Graduate School of Engineering, Tohoku University, now at JFE Steel Corp. 1) Formerly Graduate Student, Graduate School of Engineering, Tohoku University, now at Nippon Yakin Kogyo Corp. 2) Department of Metallurgy, Graduate School of Engineering, Tohoku University, Aoba-yama 02, Sendai 980-8579 Japan.…”
Section: Dissolution Behavior Of Nutrition Elements From Steelmaking mentioning
confidence: 99%
“…Seawater Nakamura et al 1) examined the propagation ability of 12 species of phytoplankton in seawater enriched with steel- Dissolution behavior of elements from 4CaO · P 2 O 5 (8.5 mass% P), 3CaO · P 2 O 5 (10.0 mass% P) and 2CaO · SiO 2 -3CaO · P 2 O 5 (2.8 mass% P) solid solution phase in artificial seawater was investigated to confirm that dissolution rate of phosphorus depends on the kind of crystal phase.…”
Section: Dissolution Experiments Of Steelmaking Slags Intomentioning
confidence: 99%
“…It was actually demonstrated that a steelmaking slag positively stimulates the growth of phytoplankters when an increase in the pH due to CaO was neutralized. 9) In case of slag enrichment in field, such neutralization can not be applied. Therefore, we examined the effect of the slags in batch cultures under freely drifting pH.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] On the other hand, there are several studies on the elution of environmentally-controlled fluorine into the seawater. [12][13][14] When steelmaking slag is being dropped into the seawater or when it has been piled on the sea bottom, the surrounding sea area might become cloudy due to Mg(OH) 2 generated by the reaction of Mg 2 + originally existed into the seawater and OH − dissolved from the steelmaking slag.…”
Section: Introductionmentioning
confidence: 99%